Description Of Clean Water Sanitation in Sipare-Pare Central Village, Merbau District, Labuhan Batu Utara Regency - Nanda, Meutia; Panjaitan, Nur Paujiah; Nurmayni; Zulkhairani, Siti; Dwitia, Suci; Ananda, Wafiq (Journal of Applied Nursing and Health, 2021)
Background: The absence of proper sanitation and clean water in sufficient quantities is the beginning of the emergence of various health problems in the community. One of the difficulties in accessing clean water is in the Sipare-pare village area, in this village, it is still a problem that the water used by the community contains a mixture of oil so that it is said to be unfit for daily use and can disturb and endanger health. This study aims to determine the description of clean water sanitation in Sipare-pare Village, Merbau District, Labuhan Batu Utara Regency Methods: The research design uses a quantitative approach with descriptive research type, the sampling technique used is the accidental sample. Methods of collecting data through in-depth interviews and observations with a cross-sectional research design. The data analysis used in this research is using univariate analysis. The research was conducted in Sipare-pare Village, Merbau District, Labuhan Batu Utara Regency Results: The results of the research conducted by the research team on 100 respondents found that clean water sanitation facilities in Pare-Pare Village are still said to be not good because there are still people whose water conditions are not clear or cloudy. Conclusion: For the quantity of water discharge sufficient to meet daily needs, in washing activities, the community uses water from drilled wells and dug wells, in contrast to the source of water used for cooking from PDAM water and for drinking water purchased refills, the water consumed is cooked. first and there are skin diseases and diarrhea caused by the consumption of clean water